Caries assessment and salivary microbial analysis in patients diagnosed with mucopolysaccharidosis - Vinod Anju; N. Sunil Raj (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: Mucopolysaccharidosis (MPS) is a group of lysosomal storage disorders that cause the deposition of polysaccharides in cells. This causes systemic and oral manifestations, which can be observed clinically and radiographically. The present study aimed to assess dental caries, the effect of salivary pH, and the change of microflora on teeth in patients diagnosed with MPS. Materials and Methods: The study included children affected with mucopolysaccharidosis (n = 50) and healthy children (n = 50) in the control group between 3 and 15 years of age. The pH of saliva and decayed, missing, and filled teeth/decayed extracted and filled teeth index were noted and recorded. For the microbial analysis, saliva was inoculated into blood agar, MacConkey agar, Candida CHROMagar, and Mitis Salivarius agar, then inspected for colony-forming units, which were counted and recorded based on the colony characteristics and gram staining. Statistical Analysis: Intergroup comparison of the test parameters was done using the Mann-Whitney test. P < 0.05 was considered statistically significant. Results: The results showed significantly higher total microbial load (P = 0.00008), streptococcus viridans species (P = 0.00001), and Candida species (P = 0.0038) in the study group. The caries incidence was also higher in the study group for both primary (P = 0.0096) and permanent dentition (P = 0.0251), and salivary pH was more acidic (P = 0.00001) in the patients diagnosed with MPS. Interpretation and Conclusion: Patients diagnosed with MPS have a higher microbial load, more acidic saliva, and subsequently, a higher caries incidence than normal healthy children. Hence, regular dental evaluation, prevention, and treatment must be integrated into their health-care regimen.